Copyright Management System to Protect the Legitimate Rights of Copy Right Owners. - Abitha, K.; Rajasekar, P. (International Journal of Engineering and Technology, 2018)
In most up-to-date days there are augmented digital technology associated digital works wherever it comes to copyright management, protection and data modification guarantee have step by step become an imperative problem. The advance of computerized copyright protection system was supported digital watermarking chiefly targeted on the rule and digital media and we are going take a look at now is about the copyright management for computerized media files. That embrace computerized watermarking, the blockchain (BC), perceptual hash function (phash), Quick Response (QR) code, and Interplanetary File System (IPFS). Among them, Blockchain is employed to firmly saves watermark data and generates timestamp proof for multiple watermarks and multiple copyrights to verify when the node was created. This theme will boost the potency of computerized watermarking technology with legitimate rights and copyright protection. During this approach, gain a peer to peer network to interact and complete copyright management and distribution of proprietary function while not requiring a third party. Nodes have faith in cryptography to verify the identity of every node and make sure the security of data. This better the safety and transparency of data and quickens the distribution of copyrighted process to facilitate within the network. To preserve the authorized rights and engrossment of every legitimate user.